1987
DOI: 10.1111/j.1440-1681.1987.tb00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Reinnervation of the Rat Vas Deferens After Vasovasostomy Following Vasectomy

Abstract: 1. Anastomosis (vasovasostomy) of epididymal and prostatic halves of vasa deferentia was carried out in rats in which unilateral or bilateral medial transection (vasectomy) had been performed 4 weeks previously. 2. Noradrenaline levels in epididymal halves of vasa deferentia, 8 weeks after anastomosis with prostatic halves, were approximately 40% of those in epididymal halves of contralateral, unoperated vasa deferentia. Catecholamine fluorescence was partially restored after anastomosis. 3. Responses of epidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In prostatic halves of transected vasa deferentia, twitch inhibition by noradrenaline was enhanced by nisoxetine to an extent similar to that in preparations of prostatic halves from contralateral unoperated vasa deferentia, indicating that in this segment there is no loss of the uptake capacity of postganglionic noradrenergic nerves, in which connections with preganglionic fibres are preserved. Indeed, in a separate group ofexperiments with unilaterally and bilaterally vasectomized rats, we have found that both the denervation, and the denervation supersensitivity, of the epididy-ma1 segment after vasectomy, can be reversed by anastomosis of the divided segments (DeGaris 1987). Uptake capacity, as determined by examination of the effects of nisoxetine upon responses to noradrenaline of epididymal segments from vasovasostomized animals, is also partially regained.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In prostatic halves of transected vasa deferentia, twitch inhibition by noradrenaline was enhanced by nisoxetine to an extent similar to that in preparations of prostatic halves from contralateral unoperated vasa deferentia, indicating that in this segment there is no loss of the uptake capacity of postganglionic noradrenergic nerves, in which connections with preganglionic fibres are preserved. Indeed, in a separate group ofexperiments with unilaterally and bilaterally vasectomized rats, we have found that both the denervation, and the denervation supersensitivity, of the epididy-ma1 segment after vasectomy, can be reversed by anastomosis of the divided segments (DeGaris 1987). Uptake capacity, as determined by examination of the effects of nisoxetine upon responses to noradrenaline of epididymal segments from vasovasostomized animals, is also partially regained.…”
Section: Discussionmentioning
confidence: 96%
“…Medial transection in vivo of the epididymal segment of the rat vas deferens leads to a progressive decline in catecholamine levels (Norberg et al, 1967), and to a loss of response of isolated preparations to transmural stimulation, for at least 6 months after surgery (DeGaris & Pennefather, 1986a, b;1987). No comparable changes occur in the prostatic half of the tissue in which the normal relationship between the pre-and postganglionic nerve fibres is preserved (DeGaris & Pennefather, 1986a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supersensitivity to noradrenaline does not occur in the prostatic segment of the operated vas deferens, which is not denervated by the surgical procedure. The supersensitivity associated with vasectomy-induced denervation of epididymal segments of the vas deferens has been shown to be partly reversed following partial re-innervation of these segments after vasovasostomy (DeGaris & Pennefather 1987b).…”
mentioning
confidence: 99%